Summary Record of Discussions of the National Development Council (NDC) Meetings Five Decades of Nation Building (Fifty NDC Meetings) Vol - V (45th To 50th Meetings) - Planning Commission (Planning Commission, 1993)
Shri Pranab Mukherjee, Deputy Chairman, Planning Commission welcomed the participants and apprised them of the main agenda item, namely, the Report of the Committee on Austerity set up under the Chairmanship of Shri Biju Patnaik, Chief Minister of Orissa, in pursuance of the decision taken by the National Development Council at its forty-third meeting held in December, 1991. to examine the possibilities of reducing State Governments' expenditure. He informed the Council that though the Report of the Committee on Austerity would be the main item on the agenda for consideration and approval, reports of the three other NDC Committees, viz., Committees on Population, Employment and Literacy were also being presented for consideration by the NDC. Keeping in view both the amount of work put in by these Committees and the many valuable recommendations made by them on the critical areas of population, employment and literacy, he requested the Council to consider these Reports also subject to the availability of time and authorise the concerned administrative Ministries/Departments initiate action for implementing the recommendations contained in them. He also requested the members to convey to the Planning Commission in writing their views and suggestions so that they could be placed before the NDC in its next meeting.
Government of India Planning Commission
Government of India Planning Commission